Targeting tumor-associated macrophages in gastric cancer progression and therapy: insights from molecular mechanisms to therapeutic applications - Wan, ChengTao; Deng, Jie; Zhu, Yu; Wan, Li; Xu, Linyue; Chen, Qiuyan; Zou, Can; Huang, Ju (Frontiers in Pharmacology, 2025)
Gastric cancer (GC) is the fifth most common malignant tumor that imposes heavily public health burdens worldwide. Systemic therapies for gastric cancer (GC), such as chemotherapy, targeted therapy, and immunotherapy, have undergone significant advancements. Nevertheless, the extensive application of anti-cancer agents has resulted in an increasing array of challenges related to drug resistance, presenting a substantial barrier in GC treatment. Tumor-associated macrophages (TAMs) as essential immunomodulators within the tumor immune microenvironment (TIME) of GC, providing novel therapeutic targets due to their capacity for plasticity in reaction to environmental signals. They create a complex network of communication with various immune and stromal cell types, thereby contributing to the immunosuppressive nature of the TME in GC. In this review, we establish the map of the origin and polarization of macrophages in GC. During the process of carcinogenesis, macrophages undergo dynamic phenotypic transitions. Additionally, the interactions between TAMs and tumor cells significantly influence the progression of GC, affecting tumor growth, metastasis, angiogenesis, and drug resistance. Furthermore, this intricate immunomodulatory axis notably enhances resistance to immunotherapy, suggesting that targeting TAMs presents substantial therapeutic opportunities for patients with GC. Approaches such as TAM elimination, TAM repolarization, and CAR-M therapy have been validated in numerous studies. We also elaborate on the challenges faced by the development of targeting TAMs, which may provide innovative perspectives on the GC treatment.